If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -4) * x = 100 Reorder the terms: (-4 + 2x) * x = 100 Reorder the terms for easier multiplication: x(-4 + 2x) = 100 (-4 * x + 2x * x) = 100 (-4x + 2x2) = 100 Solving -4x + 2x2 = 100 Solving for variable 'x'. Reorder the terms: -100 + -4x + 2x2 = 100 + -100 Combine like terms: 100 + -100 = 0 -100 + -4x + 2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-50 + -2x + x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-50 + -2x + x2)' equal to zero and attempt to solve: Simplifying -50 + -2x + x2 = 0 Solving -50 + -2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '50' to each side of the equation. -50 + -2x + 50 + x2 = 0 + 50 Reorder the terms: -50 + 50 + -2x + x2 = 0 + 50 Combine like terms: -50 + 50 = 0 0 + -2x + x2 = 0 + 50 -2x + x2 = 0 + 50 Combine like terms: 0 + 50 = 50 -2x + x2 = 50 The x term is -2x. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2x + 1 + x2 = 50 + 1 Reorder the terms: 1 + -2x + x2 = 50 + 1 Combine like terms: 50 + 1 = 51 1 + -2x + x2 = 51 Factor a perfect square on the left side: (x + -1)(x + -1) = 51 Calculate the square root of the right side: 7.141428429 Break this problem into two subproblems by setting (x + -1) equal to 7.141428429 and -7.141428429.Subproblem 1
x + -1 = 7.141428429 Simplifying x + -1 = 7.141428429 Reorder the terms: -1 + x = 7.141428429 Solving -1 + x = 7.141428429 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 7.141428429 + 1 Combine like terms: -1 + 1 = 0 0 + x = 7.141428429 + 1 x = 7.141428429 + 1 Combine like terms: 7.141428429 + 1 = 8.141428429 x = 8.141428429 Simplifying x = 8.141428429Subproblem 2
x + -1 = -7.141428429 Simplifying x + -1 = -7.141428429 Reorder the terms: -1 + x = -7.141428429 Solving -1 + x = -7.141428429 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = -7.141428429 + 1 Combine like terms: -1 + 1 = 0 0 + x = -7.141428429 + 1 x = -7.141428429 + 1 Combine like terms: -7.141428429 + 1 = -6.141428429 x = -6.141428429 Simplifying x = -6.141428429Solution
The solution to the problem is based on the solutions from the subproblems. x = {8.141428429, -6.141428429}Solution
x = {8.141428429, -6.141428429}
| 3x/(x^2-x-20) | | 3x/x^2-x-20 | | 1nx=6 | | 2x-4*x=100 | | C=8pieg | | y=-3z-4 | | 1/(3y)=1/24 | | 3(7+w)=2(6+w) | | -25=4x-4 | | 7.4x-3.8=18.4 | | 6(x+4)+2=8x-2(x-5) | | 3x+4x-4=24 | | -2x+35=2x+15 | | Cos(x)-Cos^3(x)= | | 36x-9/2x^2 | | 3x(x+2)=7 | | 3x(x-2)=7 | | 8(x+1)+4=2x+6(2+x) | | 6x-48=2x+12 | | 3n=12-3n | | 100-4q=10+q | | 2x+78=68 | | 6(8n-1)+7=8(6n+8) | | 3y-0.5=1.4y+3.1 | | 72x-9/2x^2 | | M/4=-4.1 | | 3x-8y+45=0 | | -x+47=3x+15 | | t/-8=16.2 | | 4x+3y=14-y | | 4/5×n=26 | | B-4.25=-16.5 |